PEMBERDAYAAN KELUARGA BERBASIS MASJID MELALUI KKN TEMATIK POSDAYA DI MASJID AR-ROYYAN DUSUN KARANGASEM DESA ALASMALANG - Yeni Rokhilawati (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2019)
This community devotion is a mentoring in the field of economics and environment, religious fields, health sector, and education field. KKN is one form of devotion to the community that is still needed by society. A comprehensive understanding of the cultural character and social condition of the community where KKN is absolutely necessary, as part of an effort to accelerate the adaptation and socialization process. The placement of KKN locations in the village will be highly appreciated, more than institutions based on Islamic and religious approaches will be easy in adapting to the conditions of the local community. The solidarity and togetherness between each member of the KKN team itself before implementing the program that is designed is the key to the success and smoothness of the program itself.